2018
DOI: 10.1655/herpetologica-d-17-00044.1
|View full text |Cite
|
Sign up to set email alerts
|

Movement and Habitat Use of Eastern Hellbenders (Cryptobranchus alleganiensis alleganiensis) Following Population Augmentation

Abstract: With amphibian declines at crisis levels, translocations, including population augmentations, are commonly used for amphibian conservation. Eastern Hellbenders (Cryptobranchus alleganiensis alleganiensis) have declined to low densities in many areas of their range, making them ideal candidates for population augmentation. Both wild adults and captive-reared juveniles have been used for augmentations, but their suitability has never been directly compared. Herein, we use radio telemetry with Eastern Hellbenders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Differences in dispersal between age‐classes during translocations have been observed in other species. Captive‐bred juvenile eastern hellbenders ( Cryptobranchus alleganiensis alleganiensis ) have shown lower site fidelity in translocations compared to wild born translocated adults (60–90%, respectively; McCallen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in dispersal between age‐classes during translocations have been observed in other species. Captive‐bred juvenile eastern hellbenders ( Cryptobranchus alleganiensis alleganiensis ) have shown lower site fidelity in translocations compared to wild born translocated adults (60–90%, respectively; McCallen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing translocation of wild adult and captive‐bred juvenile eastern hellbenders found survival rates were lower in juveniles (Kraus et al 2017). Site fidelity was also lower in juvenile eastern hellbenders compared to adults (McCallen et al 2018). However, in a translocation of wild adult and captive‐reared juvenile tuatara, recapture rates were similar; 56% for juveniles and 61% for adults (Nelson et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some hellbender population augmentation or reintroduction efforts have been "soft releases" (Boerner, 2014;Kocher, 2019;B. T. Kraus et al, 2017;McCallen et al, 2018). For example, eastern hellbender releases in the Allegheny River drainage in New York (Boerner, 2014;Kocher, 2019) have included soft releases using both artificial nest boxes (Briggler & Ackerson, 2012) and wire mesh cages.…”
Section: Site B2 Headstart Populationmentioning
confidence: 99%
“…Wild hellbenders are sedentary, typically spending most of their time within 30-40 m of the same stream reach (Foster et al, 2009;Nickerson & Mays, 1973). Headstart hellbenders fitted with telemetry units and tracked for short time periods have been shown to have lower site fidelity (60%) than their adult resident (100%) and translocate (90%) counterparts (McCallen et al, 2018). showed that Missouri headstarts dispersed within 550 m of release sites with most individuals dispersing <50 m. Boerner (2014) and Kocher (2019) estimated average (±SE) cumulative movement distances for New York headstarts at 653 ± 138 m and 1102 ± 267 m, respectively, and B. T. Kraus et al (2017) documented a captive reared individual moving 1.3 km from its initial release site.…”
Section: Site B2 Headstart Populationmentioning
confidence: 99%